Competing processes of micellization and fibrillization in native and reduced casein proteins. Issue 32 (28th July 2016) - Portnaya, Irina; Avni, Sharon; Kesselman, Ellina; Boyarski, Yoav; Sukenik, Shahar; Harries, Daniel; Dan, Nily; Cogan, Uri; Danino, Dganit
Abstract : Competition between micellization and fibrillization in milk caseins, intrinsically disordered proteins (IDPs). Abstract : Kappa-casein (κCN) and beta-casein (βCN) are disordered proteins present in mammalian milk. In vitro, βCN self-assembles into core–shell micelles. κCN self assembles into similar micelles, as well as into amyloid-like fibrils. Recent studies indicate that fibrillization can be suppressed by mixing βCN and κCN, but the mechanism of fibril inhibition has not been identified. Examining the interactions of native and reduced kappa-caseins (N-κCN and R-κCN) with βCN, we expose a competition between two different self-assembly processes: micellization and fibrillization. Quite surprisingly, however, we find significant qualitative and quantitative differences in the self-assembly between the native and reduced κCN forms. Specifically, thermodynamic analysis reveals exothermic demicellization for βCN and its mixtures with R-κCN, as opposed to endothermic demicellization of N-κCN and its mixtures with βCN at the same temperature. Furthermore, with time, R-κCN/βCN mixtures undergo phase separation into pure βCN micelles and R-κCN fibrils, while in the N-κCN/βCN mixtures fibril formation is considerably delayed and mixed micelles persist for longer periods of time. Fibrils formed in N-κCN/βCN mixtures are shorter and more flexible than those formed in R-κCN/βCN systems. Interestingly, in the N-κCN/βCN mixtures, the sugar moieties of N-κCN oligomers seem to organize on the mixed micelles surface in a manner similar to the organization of κCN in milk casein micelles.